Issues and Challenges of Implementing Special Education (SPED) Curriculum in the Philippines: A Systematic Literature Review - Espeño, Sheena; Babiano, Emilia H.; Bucoy, May Lanie R.; Busime, Eleonor L.; De Borja, Joanna Marie A. (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
This systematic literature review examines the issues and challenges in implementing the Special Education (SPED) curriculum in the Philippines. Despite legislative efforts, numerous obstacles hinder effective implementation, including inadequate funding, insufficient teacher training, curriculum inflexibility, social stigma, and infrastructural barriers. This review synthesizes findings from various academic articles, government reports, and organizational publications to comprehensively understand these challenges. It recommends policy enhancements, resource allocation, teacher training, curriculum adaptation, and stakeholder involvement to improve SPED implementation in the Philippines. The research uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to determine and choose the articles used in this systematic literature review. From over a thousand related articles, the researchers narrowed it down to fifteen (15) related articles following inclusion and exclusion criteria. The report offers evidence-based recommendations to address these difficulties, with the goal of policy reforms and improving their efficacy.